qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Relationship between roots and coefficients
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = \left ( 3 x - 1 \right ) \left ( x - 1 \right )$
$y = 96$
$x$Intercept
$\left ( \dfrac { 1 } { 3 } , 0 \right )$, $\left ( 1 , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
Minimum
$\left ( \dfrac { 2 } { 3 } , - \dfrac { 1 } { 3 } \right )$
Standard form
$y = 3 \left ( x - \dfrac { 2 } { 3 } \right ) ^ { 2 } - \dfrac { 1 } { 3 }$
$\left( 3x-1 \right) \left( x-1 \right) = 96$
$\begin{array} {l} x = - 5 \\ x = \dfrac { 19 } { 3 } \end{array}$
Find solution by method of factorization
$\left ( 3 x - 1 \right ) \left ( x - 1 \right ) = \color{#FF6800}{ 96 }$
$ $ Move the expression to the left side and change the symbol $ $
$\left ( 3 x - 1 \right ) \left ( x - 1 \right ) - 96 = 0$
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$ $ Expand the expression $ $
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 95 } = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 95 } = 0$
$acx^{2} + \left(ad + bc\right)x +bd = \left(ax + b\right)\left(cx+d\right)$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 19 } \right ) = 0$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 19 } \right ) = \color{#FF6800}{ 0 }$
$ $ If the product of the factor is 0, at least one factor should be 0 $ $
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 19 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 19 } = \color{#FF6800}{ 0 } \end{array}$
$ $ Solve the equation to find $ x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 19 } { 3 } } \end{array}$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = - 5 \end{array}$
Solve quadratic equations using the square root
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = 96$
$ $ Organize the expression $ $
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = 96$
$3 x ^ { 2 } - 4 x + 1 = \color{#FF6800}{ 96 }$
$ $ Move the expression to the left side and change the symbol $ $
$3 x ^ { 2 } - 4 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$3 x ^ { 2 } - 4 x + \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$ $ Subtract $ 96 $ from $ 1$
$3 x ^ { 2 } - 4 x \color{#FF6800}{ - } \color{#FF6800}{ 95 } = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 95 } = \color{#FF6800}{ 0 }$
$ $ Divide both sides by the coefficient of the leading highest term $ $
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 95 } { 3 } } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 95 } { 3 } } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 95 } { 3 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 2 } { 3 } \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 95 } { 3 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x - \dfrac { 2 } { 3 } \right ) ^ { 2 } = \color{#FF6800}{ \dfrac { 95 } { 3 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 2 } { 3 } \right ) ^ { 2 } = \dfrac { 95 } { 3 } + \left ( \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$ $ When raising a fraction to the power, raise the numerator and denominator each to the power $ $
$\left ( x - \dfrac { 2 } { 3 } \right ) ^ { 2 } = \dfrac { 95 } { 3 } + \dfrac { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 95 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 ^ { 2 } } { 3 ^ { 2 } } }$
$ $ Organize the expression $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 289 } { 9 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 289 } { 9 } }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 289 } { 9 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 289 } { 9 } } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 17 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 17 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 17 } { 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 3 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 17 } { 3 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 17 } { 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 } { 3 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 17 } { 3 } } \end{array}$
$ $ Organize the expression $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 19 } { 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \end{array}$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = - 5 \end{array}$
Calculate using the quadratic formula
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = 96$
$ $ Organize the expression $ $
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = 96$
$3 x ^ { 2 } - 4 x + 1 = \color{#FF6800}{ 96 }$
$ $ Move the expression to the left side and change the symbol $ $
$3 x ^ { 2 } - 4 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 96 } = \color{#FF6800}{ 0 }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm \sqrt{ \left ( - 4 \right ) ^ { 2 } - 4 \times 3 \times \left ( - 95 \right ) } } { 2 \times 3 } }$
$x = \dfrac { 4 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times \left ( - 95 \right ) } } { 2 \times 3 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 4 \pm \sqrt{ 4 ^ { 2 } - 4 \times 3 \times \left ( - 95 \right ) } } { 2 \times 3 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm \sqrt{ 4 ^ { 2 } - 4 \times 3 \times \left ( - 95 \right ) } } { 2 \times 3 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm \sqrt{ 1156 } } { 2 \times 3 } }$
$x = \dfrac { 4 \pm \sqrt{ \color{#FF6800}{ 1156 } } } { 2 \times 3 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { 4 \pm \color{#FF6800}{ 34 } } { 2 \times 3 }$
$x = \dfrac { 4 \pm 34 } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } }$
$ $ Multiply $ 2 $ and $ 3$
$x = \dfrac { 4 \pm 34 } { \color{#FF6800}{ 6 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm 34 } { 6 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 + 34 } { 6 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 - 34 } { 6 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 34 } } { 6 } \\ x = \dfrac { 4 - 34 } { 6 } \end{array}$
$ $ Add $ 4 $ and $ 34$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 38 } } { 6 } \\ x = \dfrac { 4 - 34 } { 6 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 38 } { 6 } } \\ x = \dfrac { 4 - 34 } { 6 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 19 } { 3 } } \\ x = \dfrac { 4 - 34 } { 6 } \end{array}$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \dfrac { \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 34 } } { 6 } \end{array}$
$ $ Subtract $ 34 $ from $ 4$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 30 } } { 6 } \end{array}$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \color{#FF6800}{ \dfrac { - 30 } { 6 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \color{#FF6800}{ \dfrac { - 5 } { 1 } } \end{array}$
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \dfrac { - 5 } { \color{#FF6800}{ 1 } } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = \dfrac { 19 } { 3 } \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \end{array}$
$ $ 2 real roots $ $
Find the number of solutions
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = 96$
$ $ Organize the expression $ $
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = 96$
$3 x ^ { 2 } - 4 x + 1 = \color{#FF6800}{ 96 }$
$ $ Move the expression to the left side and change the symbol $ $
$3 x ^ { 2 } - 4 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$3 x ^ { 2 } - 4 x + \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$ $ Subtract $ 96 $ from $ 1$
$3 x ^ { 2 } - 4 x \color{#FF6800}{ - } \color{#FF6800}{ 95 } = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 95 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 95 } \right )$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times \left ( - 95 \right )$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$D = 4 ^ { 2 } - 4 \times 3 \times \left ( - 95 \right )$
$D = \color{#FF6800}{ 4 } ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times \left ( - 95 \right )$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 16 } - 4 \times 3 \times \left ( - 95 \right )$
$D = 16 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 95 } \right )$
$ $ Multiply the numbers $ $
$D = 16 + \color{#FF6800}{ 1140 }$
$D = \color{#FF6800}{ 16 } \color{#FF6800}{ + } \color{#FF6800}{ 1140 }$
$ $ Add $ 16 $ and $ 1140$
$D = \color{#FF6800}{ 1156 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 1156 }$
$ $ Since $ D>0 $ , the number of real root of the following quadratic equation is 2 $ $
$ $ 2 real roots $ $
$\alpha + \beta = \dfrac { 4 } { 3 } , \alpha \beta = - \dfrac { 95 } { 3 }$
Find the sum and product of the two roots of the quadratic equation
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) = 96$
$ $ Organize the expression $ $
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = 96$
$3 x ^ { 2 } - 4 x + 1 = \color{#FF6800}{ 96 }$
$ $ Move the expression to the left side and change the symbol $ $
$3 x ^ { 2 } - 4 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$3 x ^ { 2 } - 4 x + \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 96 } = 0$
$ $ Subtract $ 96 $ from $ 1$
$3 x ^ { 2 } - 4 x \color{#FF6800}{ - } \color{#FF6800}{ 95 } = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 95 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 4 } { 3 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 95 } { 3 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 4 } { 3 } } , \alpha \beta = \dfrac { - 95 } { 3 }$
$ $ Solve the sign of a fraction with a negative sign $ $
$\alpha + \beta = \color{#FF6800}{ \dfrac { 4 } { 3 } } , \alpha \beta = \dfrac { - 95 } { 3 }$
$\alpha + \beta = \dfrac { 4 } { 3 } , \alpha \beta = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 95 } } { 3 }$
$ $ Move the minus sign to the front of the fraction $ $
$\alpha + \beta = \dfrac { 4 } { 3 } , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 95 } { 3 } }$
$ $ 그래프 보기 $ $
Graph
Solution search results
search-thumbnail-If the sum of two consecutive 
numbers is $45$ and one number is $X$ 
.This statement in the form of 
equation $1s:$ 
$\left(1$ Point) $\right)$ 
$○5x+1$ $1eft\left(x+1$ $r1gnt\right)=45s$ 
$○sx+1ef\left(x+2$ $r1gnt\right)=145s$ 
$sx+1x=45s$
7th-9th grade
Algebra
search-thumbnail-$s|ef\left(-1n$ $\left($ }\right)^{50}\ $\right)$ \ | | is\ equal\ to\ $S$ 
$s1S$ 
$S-1S$ 
$s2S$ 
$s50s$
7th-9th grade
Other
search-thumbnail-Given the set of ordered pairs $\left(\left(-7.0\right),\left(-6,5\right),\left(-5,-3\right),\left(-1,2\right)$ $\left(1,6\right),\left(2,-2\right)$ $\left(5,3\right)\left(7,-8\right)\right)$ 
Find f(7)fAleft(7\right) 
O a 
O b -8 
6. 
$5$
7th-9th grade
Algebra
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo